A bit late to add my contribution. I think there is another (longer) scheme to demonstrate the EM algorithm that uses the KL divergence. What is sure is that the Jensen inequality is also used in that scheme.
The EM algorithm seeks to maximize a lower bound of a likelihood.
Let $Y=(Y_1, ..., Y_n)$ be the set of possible observations. We want to discover hidden or latent variables $X=(X_1, ..., X_n)$. Each $X_i$ is actually associated to an observation $Y_i$, and we suppose here that the hidden variable are drawn from $\{1,...,c\}$.
We introduce $q=(q_1,...,q_n)$ s.t $\forall i \in \{1,...,n\}$, $q_i$ approximates somehow $P(X_i|Y_i, \theta)$.
In the following, $P(X_{ij}|Y_i, \theta)$ is equivalent to $P(X_{i}=j|Y_i, \theta)$.
We denote by $\theta$ the hyperparameters of our probabilities.
We would like to maximize the following log-likelihood
\begin{equation}
\mathcal{L}(\theta) = \sum\limits_{i=1}^n \text{log}(P(Y_i|\theta))
\end{equation}
However, solving directly on all the unknowns, the problem would be intractable since:
\begin{equation}
\mathcal{L}(\theta) = \sum\limits_{i=1}^n \text{log}( \sum\limits_{j=1}^c P(Y_i, X_{ij}|\theta))
\end{equation}
Fortunately, it is possible to show that:
\begin{equation}
\mathcal{L}(\theta) \geq \text{LB}(\theta)
\end{equation}
With
\begin{equation}
\text{LB} = \mathcal{H}(q) + \mathcal{E}(Y, X, q, \theta)
\end{equation}
$\mathcal{H}(q)$ is an entropy term that will force the mass distribution of $q$ to spread, so it does not concentrate on a single location
$\mathcal{E}(Y, X, q, \theta)$ is an energy term that encourages the mass distribution of $P(Y,X|\theta)$ to focus on location where the model puts high probability
I'd say the entropy term could be seen as a regularizer, that encourage solutions that do not overfit.
I'd say introducing the $q_i$ s help separate the unknowns and optimize them alternatively.
I think you can find more here, that is where I found a reliable explanation of those terms.
Expressions of those two terms can be found below.
Proof Sketch
We would like to maximize the following log-likelihood
\begin{equation}
\mathcal{L}(\theta) = \sum\limits_{i=1}^n \text{log}(P(Y_i|\theta))
\end{equation}
Now let's focus on each term, using the lemma provided at the end, we have:
\begin{equation}
\text{log}(P(Y_i|\theta)) =\text{KL}(q_i(X_i) || P(X_i|Y_i, \theta)) + \sum\limits_{j=1}^c q_{i}(X_{ij}) \, \text{log}(\frac{P(Y_i, X_{ij}|\theta)}{q_{i}(X_{ij})})
\end{equation}
Then:
\begin{equation}
\mathcal{L}(\theta) = \sum\limits_{i=1}^n \text{KL}(q_i || P(X_{i}|Y_i, \theta)) + \sum\limits_{i=1}^n \sum\limits_{j=1}^c q_{i}(X_{ij}) \, \text{log}(\frac{P(Y_i, X_{ij}|\theta)}{q_{i}(X_{ij})})
\end{equation}
Now the KL divergence is always non-negative, due to the Jensen Inequality, so :
\begin{equation}
\mathcal{L}(\theta) \geq \sum\limits_{i=1}^n \sum\limits_{j=1}^c q_{i}(X_{ij}) \, \text{log}(\frac{P(Y_i, X_{ij}|\theta)}{q_{i}(X_{ij})})
\end{equation}
We can finally split this lower bound, let us call it LB, in two terms:
\begin{equation}
\text{LB} = \sum\limits_{i=1}^n \text{H}(q_i) + \sum\limits_{i=1}^{n} \sum\limits_{j=1}^{c} q_i(X_{ij}) \text{log}(P(Y_i, X_{ij}|\theta))
\end{equation}
\begin{equation}
\text{LB} = \mathcal{H}(q) + \mathcal{E}(Y, X, q, \theta)
\end{equation}
Lemma
Let's show that the following holds:
\begin{equation}
\text{log}(p(x)) = \text{KL}(q(z) || p(z|x)) + \mathbb{E}_{q(z)} [\text{log}(p(x,z) - log(q(z))]
\end{equation}
with $p$, $q$ all probabilities.
Now let's focus on each term, we have:
\begin{equation}
\text{log}(p(x)) = \sum\limits_{z} q(z) \, \text{log}(p(x))
\end{equation}
We next make use of Bayes' rule:
\begin{equation}
\text{log}(p(x)) = \sum\limits_{z} q(z) \, \text{log}(\frac{p(x,z)}{p(z|x)})
\end{equation}
We can make use of a little trick:
\begin{equation}
\text{log}(p(x)) = \sum\limits_{z} q(z) \, \text{log}(\frac{q(z) \, p(x,z)}{p(z|x) \, q(z)})
\end{equation}
We can separate into two terms:
\begin{equation}
\text{log}(p(x)) = \sum\limits_{z} q(z) \, \text{log}(\frac{q(z)}{p(z|x)}) + \sum\limits_{z} q(z) \, \text{log}(\frac{p(x,z)}{q(z)})
\end{equation}
We recognize the KL divergence...
\begin{equation}
\text{log}(p(x)) = \text{KL}(q(z)||p(z|x)) + \mathbb{E}_{q(z)} [\text{log}(p(x,z) - log(q(z))]
\end{equation}